2017
DOI: 10.1152/ajpregu.00361.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow autoregulation in ischemic heart failure

Abstract: Patients with ischemic heart failure (iHF) have a high risk of neurological complications such as cognitive impairment and stroke. We hypothesized that iHF patients have a higher incidence of impaired dynamic cerebral autoregulation (dCA). Adult patients with iHF and healthy volunteers were included. Cerebral blood flow velocity (CBFV, transcranial Doppler, middle cerebral artery), end-tidal CO (capnography), and arterial blood pressure (Finometer) were continuously recorded supine for 5 min at rest. Autoregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 40 publications
2
44
1
3
Order By: Relevance
“…In a longitudinal nondemented population-based study with echocardiography assessments at baseline and after five years follow up, van den Hurk et al concluded that cognitive decline can be observed in the early stages of left ventricular dysfunction and heart failure 11 . It seems that from the above-mentioned mechanisms, impaired cerebrovascular autoregulation and endothelial dysfunction are possibly more affected with even mild reduction of the ejection fraction 24 . Our patients were selected from referrals to a cardiac catheterization unit.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal nondemented population-based study with echocardiography assessments at baseline and after five years follow up, van den Hurk et al concluded that cognitive decline can be observed in the early stages of left ventricular dysfunction and heart failure 11 . It seems that from the above-mentioned mechanisms, impaired cerebrovascular autoregulation and endothelial dysfunction are possibly more affected with even mild reduction of the ejection fraction 24 . Our patients were selected from referrals to a cardiac catheterization unit.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a brachial mean BP ≥60 mm Hg is thought to afford an adequate cerebral blood flow. Cerebral blood flow autoregulation may be affected in advanced age,49 by endotheliopathy, hypertension, diabetes mellitus,50 heart failure,51 hypocapnia, alkalosis, sympathetic arousal, autonomic failure,52 early after head injury, during an acute ischaemic stroke or during sepsis 53. The cerebral flow reserve also depends on the existence of cerebral small and large artery disease.…”
Section: Bp Goalsmentioning
confidence: 99%
“…In a healthy cardiovascular system, cerebral flow rate changes slightly within a range between 60 and 140 mm Hg of arterial blood pressure . However, in the heart failure patients' clinical data indicates that cerebral flow autoregulation function may be impaired and there might be a mild to moderate average cerebral flow rate reduction . Moreover, cerebral flow may reduce by up to 30 percent although arterial blood pressure remains within the autoregulation zone .…”
mentioning
confidence: 99%